The usefulness of the Sustainable Finance Disclosure Regulation - An explorative study into its shortcomings and challenges - Talitha Saez Cardoso; Ralph ter Hoeven (MAB)
The Sustainable Finance Disclosure Regulation (SFDR)1 aims to enhance transparency and curb greenwashing by standardizing sustainability disclosures. Despite its ambitious goals, the SFDR faces challenges and criticisms regarding its practical implementation and effectiveness. This article delves into these issues through an exploration of the European Commission consultations, articles, and recommendations from entities such as the Platform on Sustainable Finance (PSF), the European Sustainable Investment Forum (Eurosif), and the Dutch Authority for the Financial Markets (AFM). Our study identifies key areas where the SFDR currently falls short while suggestions for improving the effectiveness of disclosures are provided.